Modulation of Nrf2 by Olive Oil and Wine Polyphenols and Neuroprotection - Miriam Martínez-Huélamo; Jose Rodríguez-Morató; Anna Boronat; Rafael de la Torre (Antioxidants, 2017)
Strong adherence to a Mediterranean diet is associated with improved cognitive function and a lower prevalence of mild cognitive impairment. Olive oil and red wine are rich sources of polyphenols which are responsible in part for the beneficial effects on cognitive functioning. Polyphenols induce endogenous antioxidant defense mechanisms by modulating transcription factors such as the nuclear factor (erythroid-derived 2)-like 2 (Nrf2). This review discusses the scientific data supporting the modulating effect of olive oil and red wine polyphenols on Nrf2 expression, and the potential health benefits associated with cognitive functioning.